2020
DOI: 10.48550/arxiv.2010.01143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the "Lensing is Low" of BOSS Galaxies

Abstract: Recently, Leauthaud et al discovered that the small-scale lensing signal of Baryon Oscillation Spectroscopic Survey (BOSS) galaxies is up to 40% lower than predicted by the standard models of the galaxy-halo connections that reproduced the observed galaxy stellar mass function (SMF) and clustering. We revisit such "lensing is low" discrepancy by performing a comprehensive Halo Occupation Distribution (HOD) modelling of the SMF, clustering, and lensing of BOSS LOWZ and CMASS samples at Planck cosmology. We allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…Recently, Zu (2020) claimed that the lensing-is-low tension can be solved on small scales for both the CMASS sample analysed in Leauthaud et al (2017) and Yuan et al (2020b) and a LOWZ sub-sample very similar to the one studied in this work. The author can fit the large-scale clustering and lensing on small scales by predicting a large fraction of satellites in both galaxies samples.…”
Section: Lensing Is Lowmentioning
confidence: 58%
“…Recently, Zu (2020) claimed that the lensing-is-low tension can be solved on small scales for both the CMASS sample analysed in Leauthaud et al (2017) and Yuan et al (2020b) and a LOWZ sub-sample very similar to the one studied in this work. The author can fit the large-scale clustering and lensing on small scales by predicting a large fraction of satellites in both galaxies samples.…”
Section: Lensing Is Lowmentioning
confidence: 58%
“…Recent work has shown that modifying the standard HOD formalism to include assembly bias does reduce the "lensing is low" discrepancy (e.g. Yuan et al 2021;Lange et al 2021;Zu 2020). The ability of relatively computationally efficient physics-based models, such as SAMs, to qualitatively reproduce the assembly bias signal seen in more sophisticated numerical hydrodynamic simulations is very promising for developing techniques to create large volume mock galaxy catalogs that are consistent with both lensing and galaxy clustering as well as other cosmological probes.…”
Section: Discussionmentioning
confidence: 99%
“…We find the best-fitting values to be {lg 𝑀 ℎ =13.19, 𝑐=5.1, 𝑏=1.15, 𝜅=0.63, 𝛼=1.2}, and the best-fitting predictions of the total (blue solid) and resolved (red solid) signals are shown in the left main panel of Figure 5. The bias value is slightly higher than predicted for haloes with lg 𝑀 ℎ =13.19, primarily because a good fraction of the LRGs are satellite galaxies inside massive haloes (Zu 2020). Both predictions are in excellent agreement with the measurements, as demonstrated by the ratios between data and predictions in the left bottom panel of Figure 5.…”
Section: Reconstruct 3d Galaxy-cloud Cross-correlationmentioning
confidence: 61%